2015
DOI: 10.4049/jimmunol.1401923
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Progesterone Directly Upregulates Vitamin D Receptor Gene Expression for Efficient Regulation of T Cells by Calcitriol

Abstract: The two nuclear hormone receptor ligands progesterone and vitamin D (vit.D) each play important roles in regulating T cells. The mechanism that connects these two hormones in regulating T cells has not been established. We report here that progesterone is a novel inducer of vit.D receptor (VDR) in T cells and makes T cells highly sensitive to calcitriol. At the molecular level, the induction by progesterone is mediated by two progesterone receptor binding elements in the intron region after the first non-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…This process is important for the menstrual cycle, mammary gland development, and pregnancy maintenance. Recently, we discovered that P4 induces vitamin D receptor (VDR) expression (Thangamani et al, 2015). We observed this regulation in T cells, and therefore, the immediate impact of our finding is on immune regulation (Fig.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…This process is important for the menstrual cycle, mammary gland development, and pregnancy maintenance. Recently, we discovered that P4 induces vitamin D receptor (VDR) expression (Thangamani et al, 2015). We observed this regulation in T cells, and therefore, the immediate impact of our finding is on immune regulation (Fig.…”
supporting
confidence: 57%
“…We found that calcitriol becomes highly effective in regulating T cells when P4 is present at the same time (Thangamani et al, 2015). P4 enhances the T-cell response to calcitriol by three to five times.…”
Section: Vitamin D Receptor Induction By P4 and Its Impact On The Immmentioning
confidence: 74%
See 2 more Smart Citations
“…3 guided in concert T cells from a pro-inflammatory (Th1 and Th17) to a more regulatory profile [434] . A synergistic effect of 1,25(OH) 2 …”
mentioning
confidence: 99%